Molecular characterization and expression analysis of anti-Müllerian hormone in common carp (Cyprinus carpio) adult testes - Oliveira, Marcos A. [UNESP] (2021)
Anti-Müllerian hormone (Amh) is a member of the transforming growth factor-β (Tgf-β) superfamily required in the regression of Müllerian ducts during gonadal sex differentiation of higher vertebrates. Teleost fish lack Müllerian ducts, but identified Amh orthologs have been shown to exert crucial functions during sex determination and differentiation of several species of teleosts. However, the function of Amh during gametogenesis in adult fish remains poorly investigated. Therefore, to expand present knowledge on the role of Amh in teleosts, the present study aimed to isolate and clone full-length amh cDNA in the common carp, Cyprinus carpio, and examine its expression levels throughout the male reproductive cycle and in response to different hormone treatments of testicular explants. Molecular cloning and characterization showed that the common carp Amh precursor amino acid sequence shared common features to other fish Amh precursors, including a conserved C-terminus (Tgf-β domain) and a double proteolytic cleavage site (R-X-X-R-X-X-R) upstream to the Tgf-β domain. Expression analysis showed amh dimorphic expression in the adult gonads with higher expression in the testes than ovaries. In testes, amh mRNA was detected in Sertoli cells contacting different types of germ cells, although the expression was greatest in Sertoli cells associated with type A undifferentiated spermatogonia. Expression analysis during the reproductive cycle showed that amh transcripts were down-regulated during the developing phase, which is characterized by an increased proliferation of type A undifferentiated spermatogonia and Sertoli cells and appearance of spermatocytes (meiosis) in the testes. Furthermore, ex vivo experiments showed that a 7 day exposure to Fsh or estrogens was required to decrease amh mRNA levels in common carp testicular explants. In summary, this study provided information on the molecular characterization and transcript abundance of amh in common carp adult testes. Altogether, these data will be useful for further investigations on sex determination and differentiation in this species, and also to improved strategies for improved carp aquaculture, such as inhibiting precocious maturation of males.